Bis{2-methoxy-6-[( E )-(4-methylbenzyl)iminomethyl]phenolato}palladium(II) chloroform monosolvate - Bahron, Hadariah; Tajuddin, Amalina Mohd; Ibrahim, Wan Nazihah Wan; Chantrapromma, Suchada; Fun, Hoong-Kun (Acta crystallographica. Section E, Structure reports online, 2014)
In the title complex, [Pd(C 16 H 16 NO 2 ) 2 ]·CHCl 3 , the Pd II cation lies on an inversion center. One Cl atom of the CHCl 3 solvent molecule lies on a twofold axis and the C—H group is disordered with equal occupancies about this axis with the other Cl atom in a general position with full occupancy. The Pd II cation is four-coordinate and adopts a square-planar geometry via coordination of the imine N and phenolic O atoms of the two bidentate Schiff base anions. The N and O atoms of these ligands are mutually trans . The plane of the benzene ring makes a dihedral angle of 73.52 (10)° with that of the methoxyphenolate ring. In the crystal, molecules of the Pd II complex are arranged into sheets parallel to the ac plane, and the chloroform solvent molecules are located in the interstitial areas between the complex molecules. Weak intermolecular C—H...O and C—H...π interactions stabilize the packing.